Consumer Perception of Health and Wellness Products - Suhartini, Titin (Management Science Doctoral Program, Pasundan University, 2024)
This study aims to understand consumer perceptions of health and wellness products amidst growing public awareness of the importance of a healthy lifestyle. Using a qualitative approach, this research explores factors that influence consumer perceptions, such as trust, personal experience, preferences, and social influence. Data collection methods include in-depth interviews and focus group discussions (FGDs) with 20 respondents from diverse backgrounds in age, gender, and physical activity levels. A purposive sampling technique was used to ensure a relevant variety of views on health and wellness products. The collected data was analyzed using thematic analysis, producing key themes such as trust in product safety and effectiveness, preferences for natural over chemically-based products, and the influence of community and social media in shaping perceptions. The study's findings indicate that consumer perceptions of health products are significantly influenced by personal experiences and information obtained from social environments and media. Trust in the brand and the transparency of manufacturers in providing information also play an important role in shaping consumer decisions. Additionally, it was found that consumers tend to prefer products considered natural and that offer clear health claims. This research provides insights for producers in designing marketing strategies that can enhance consumer trust through transparent education and strengthen brand reputation.